2023
DOI: 10.1136/jitc-2022-006007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cbl-b in cancer immunotherapy

Abstract: Cancer immunotherapy with immune-checkpoint blockade has improved the outcomes of patients with various malignancies, yet a majority do not benefit or develop resistance. To address this unmet need, efforts across the field are targeting additional coinhibitory receptors, costimulatory proteins, and intracellular mediators that could prevent or bypass anti-PD1 resistance mechanisms. The CD28 costimulatory pathway is necessary for antigen-specific T cell activation, though prior CD28 agonists did not translate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Following, we verified the function of CBLB in colon cancer. CBLB is a proto-oncogene considered as a new target for tumor immunotherapy [ 41 ]. However, its expression in colon cancer has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Following, we verified the function of CBLB in colon cancer. CBLB is a proto-oncogene considered as a new target for tumor immunotherapy [ 41 ]. However, its expression in colon cancer has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…As a upstream gene, the HRAS which enriched in ErbB signaling pathway and JAK-STAT signaling pathway could affect on the effectiveness of immunotherapy through regulating PI3K signaling 30. Meanwhile, the gene CBLB enriched in T cell receptor signaling pathway and ErbB signaling pathway could inhibit T cell transcriptional activity and promote immune tolerance31 and had been shown to act as an intracellular checkpoint,32 Augustin et al reported that CBLB as a key downstream mediator of PD-1 and CTLA-4 signaling pathway could influence the resistant to immunotherapy 33. Gu et al found that the gene TRAF3 enriched in pathways in cancer was a suppressor of NF- κ B pathway and associated with better survival in ICIs-naïve cancer patients and better ICIs response 34.…”
Section: Discussionmentioning
confidence: 99%
“…ICIs play a crucial role in regulating the expression of Cbl-b. The costimulatory molecule CD28 promotes ubiquitination and degradation of Cbl-b, while the coinhibitory molecule CTLA-4 can induce Cbl-b expression after interaction with B7, thereby modulating various signaling pathways and amplifying T-cell activation, such as cytokine or TCR-mediated signal transduction. , In addition, the expression of Cbl-b also limits the production of IL-2 and inhibits the mitogen-activated protein kinase (MAPK)/extracellular regulated protein kinases (ERK) mediated signal transduction downstream of the IL-2 receptor, thus reducing T cells proliferation. , …”
Section: The Role Of Cbl-b In Immune Cellsmentioning
confidence: 99%